SPATIALIZATION OF FIRE OCCURRENCES IN BRAZIL WITHIN THE CONTEXT OF THE FIRE EVENTS DETECTED BY THE FIRE PANEL - Pastrana Mojica, Jack Endrick; Bernini, Henrique; de Faria, Daniela Guimarães; Hauck Antunes, Eduardo; Siqueira, Leonardo; Souza Silva, Camila; Correia Fontoura, Sarah; Rodovalho, Fernando (Ra’e Ga: o Espaço Geográfico em Análise, 2024)
The reliability of fire information in Brazil is essential for the most efficient deployment of firefighting teams. In Brazil, information from remote sensing has been fundamental in guiding the management and monitoring of fire in rural areas. During a firefighting operation and the observation of a fire or burning, the collection of data in the field becomes essential to complement the information the observation data on the ground. This research analyzed the relationship between the data collected by the institutions involved in fire control and monitoring, and the fire events provided by CENSIPAM, with the objective of carrying out a first methodological approximation of these two forms of fire data collection. The second step was to analyze the characteristics of the occurrences that were cross-referenced using the properties of the remote sensing data. To do this, it was necessary to build a model for cross-referencing data in Posts and extract data from the fire reports provided by ICMBio, PREVFOGO and the Military Fire Brigades (CBM). A low level of spatial correspondence was obtained between the occurrences collected in the field and the fire events. As a consequence,has been taken advantage of the analysis possibilities offered by remote sensing data, such as spatial parameters that reveal different occurrence patterns due to the type of fire.